The Intersection of Anthropology and Criminal Law: Insights for Policy and Practice - Ashriani, Sheilla Manzila (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
The intersection of anthropology and criminal law offers valuable insights for informing policy and practice in the criminal justice system. This article explores the dynamic relationship between anthropology and criminal law, highlighting the contributions of anthropological research to understanding crime, criminal behavior, and the functioning of legal systems. Through a qualitative approach, this study conducts a comprehensive review of relevant literature and utilizes library research methods to synthesize key findings. The analysis reveals that anthropology provides unique perspectives on cultural norms, social structures, and power dynamics that influence the formulation and application of criminal laws. By examining diverse cultural contexts, anthropologists uncover the complexities of crime and justice, shedding light on issues such as legal pluralism, cultural defense, and the role of indigenous justice systems. Furthermore, anthropological insights challenge conventional approaches to criminal justice, emphasizing the importance of context- specific interventions and culturally sensitive practices. This article identifies five key themes that emerge from the literature review: cultural relativism, legal pluralism, the social construction of crime, indigenous justice systems, and the impact of globalization on legal norms. These themes offer valuable lessons for policymakers, legal practitioners, and criminal justice professionals seeking to develop more effective and culturally responsive approaches to crime prevention, law enforcement, and criminal adjudication. By bridging the gap between anthropology and criminal law, this research contributes to a deeper understanding of the complexities of crime and justice in diverse cultural contexts.